UPAYA MENINGKATKAN MINAT BELAJAR MATEMATIKA MENGGUNAKAN MEDIA INTERAKTIF BERBASIS POWERPOINT - Nurapni Sopia (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research is motivated by the existence of teachers who have not used learning methods optimally and teachers rarely use learning media when delivering subject matter so that students' interest in learning is low. The low interest in student learning is characterized by students not paying attention to the teacher, students looking sleepy and students talking to their friends during the learning process. This study aims to describe the increase in learning interest of second grade students of SD Negeri 25 Empakan after using Powerpoint-Based Interactive Media. This study uses a qualitative descriptive approach and a form of classroom action research. The implementation process consists of 4 stages, namely: planning, implementing actions, observing and reflecting. From the results of the study obtained the average student interest in using Powerpoint-Based Interactive Media in the first cycle with a classical percentage of 52.91%. While the percentage of classical interest in learning in the second cycle increased to 97.98%. Based on the data exposure, research findings, and the discussion that has been described, it can be concluded that the use of Microsoft Powerpoint-Based Interactive Media can increase students' interest in learning.